Anplagd - Kovac̆ević, Mladen (Produkcija Horopter, 2013)
Vera, a private detective retired to the village where she grew up as shepherdess, and Pera, the know-it-all peasant of many esoteric skills, are some of the last remaining expert leaf-players in the country. Both in the autumns of their lives, they are still strongly blowing into leaves, producing amazingly unique music. Josip, an inventor of musical instruments, has set out to decode their obscure artistry and the result is 'Unplugged' - an existential allegory about music played on tree leaves, humorously rattling between the most primitive of instruments and the most universal escapism of music. Music has rarely been so offbeat.--